HUBUNGAN HASIL DIKLAT BERJENJANG TINGKAT DASAR DENGAN KINERJA GURU PENDIDIKAN ANAK USIA DINI - Elisabeth, Elisabeth; Marmawi, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the relationship of basic level of basic education with the performance of early childhood teachers in Sungai Kakap District Kubu Raya District. The method used is descriptive with quantitative approach with a total sample of 32 people. The result of the research shows that the result of the level of basic education level of early childhood teachers in Sungai Kakap sub-district of Kubu Raya Regency with the largest percentage (68.75%) is in the medium category. While the performance of teachers with the largest percentage (65.625%) also fall into the medium category ..Product Moment-0,007 correlation value. The value is compared with the value of r_ (table) with a significant level of 5%, ie df = n-2 = 32-2 = 30 obtained value r_ (table) = 0.361 (-0.007 <0.361), which means Hâ‚’ accepted and Hâ‚ rejected. Thus, in this study showed that the results of tiered level of basic education of early childhood teachers there is no positive and significant relationship with the performance of early childhood teachers in Sungai Kakap District Kubu Raya.Â Keyword : Basic Level Basic Training,Teacher Performance, Early Childhood Education.Â